Preparação de nanofibras de celulose a partir de fibras de curauá para desenvolvimento de nanocompósitos poliméricos com EVA - Corrêa, Ana Carolina (2010)
The objective of the current project was the obtainment of cellulose nanofibers from curaua fibers and their application on the development of polymeric nanocomposites with EVA. A study of cellulose extraction according to the pre-treatment of the curaua fibers (mercerization with 5, 10, 15 and 17.5% NaOH solutions), acid solution used in acid hydrolysis (sulfuric (H2SO4), hydrochloric (HCl), and a mix of them (2:1 v/v)) and temperature of hydrolysis (45oC e 60oC) was carried out. Morphological analysis presented nanofibers with needle-like morphology, and similar lengths and diameters. It was noticed that the addition of hydrochloric acid to promote hydrolysis improved thermal stability of nanofibers, if compared to those hydrolyzed with sulphuric acid only, independent of fibers pre-treatment of the fibers. Nanocomposites and composites were prepared with EVA and nanofibers or mercerized fibers, with 1, 3, 5 and 7 wt% of nanofibers and 1-30 wt% of mercerized fibers, to evaluate the effect of concentration and reinforcement of nanofibers on composites properties as compared with micrometric scale fibers. The extrusion process, to incorporation of nanofibers in EVA matrix, was not enough to disperse and break of clusters of nanofibers down, which behaved as micrometric particles with low aspect ratio, but they were well adhered to the matrix, even without the use of compatibilizers. Mechanical properties of the nanocomposites presented a small increase in elastic modulus with a decrease in strain at break. For composites with mercerized curaua fibers, the extrusion process presented good fiber dispersion. The composites showed an increase on mechanical properties, mainly elastic modulus, with the increase of fiber content, greater than 7%, but with no significant changes in thermal properties.